The variable speed drive VSD as ideal method for starting electric induction motors - Carrillo-Romero, Julio Alberto; Rojas-Boyacá, Jairo Alberto (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2013)
By programming parameters, implementation of VSD reference CFW-11, and conducting starts with electric induction motors, with different characteristics, we analyze the behavior of the variables: voltage, current, torque and engine velocity to verify that the starting VSD method is the ideal. System graphs are obtained by implementing the tool "Trend" from SuperDriveG2 software, which are analyzed to determine the behavior of the application.